Monitoring the particle size distribution of whole and skimmed milk during acidic or enzymatic coagulation process (Research, Society and Development, 2022)
The milk coagulation process can occur mainly in two ways: acidic or enzymatic coagulation, the characteristic of the gel obtained being dependent on the type of coagulation, the type of processing applied and the composition of the initial milk. Therefore, the objective of this work was to evaluate the microstructural modifications of pasteurized whole and skimmed milk through particle distribution analysis (LS), through acidic coagulation, carried out via fermentation by adding a mixed culture of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus; and enzymatic, by the addition of microbial chymosin. During the entire coagulation process, milk aliquots were removed from both coagulations until gels were obtained. The gels obtained showed differences in coagulation time and particle size distribution, in addition, the particles sizes of the skimmed milks gels showed final values in all distributions greater than that of whole milk, possibly related to the fact of casein, protein majority, be more available in the reaction medium so that the destabilization of the system occurs in both types of coagulation. When comparing the two coagulation processes for the d90 distribution, the enzymatic coagulation gels showed aggregates 12 times larger than the acid coagulation gels, demonstrating that the interaction forces for the formation of aggregates are much greater in enzymatic coagulation.